Pemeriksaan Skrining Alternatif PAP SMEAR - Parwati, Dewi; Arianto, Steven; Pannyiwi, Rahmat; Rahmat, Rezqiqah Aulia; Sabriana, Riska; Rosida, Rosida (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
The incidence of cervical cancer in Indonesia reached 20,928 and cervical cancer is in second place after breast cancer. Pap smear is a microscopic examination of cells obtained from a cervical smear to detect early changes or abnormalities in the cervix before the cells become cancer and can be carried out by health workers other than gynecologists. The purpose of a pap smear is: a). Try to find cells that are not normal and can develop into cervical cancer. b). A tool to detect pre-cervical cancer symptoms for someone who has not yet suffered from cancer. c). Know the abnormalities that occur in cervical cancer cells. d). To determine the level of malignancy of the cancer cells, the examination is carried out by looking at the cervix which has been treated with 3-5% acetic acid inspectively. The methods used with the descriptive approach include: Conducting counseling about early detection of cervical cancer, Carrying out questions and answers about cervical cancer and the IVA test, Carrying out initial screening, namely no menstruation during the IVA test, no intercourse for 2 days, Carrying out an anamnesis on each - each respondent. Carrying out IVA tests in communities that have met the requirements for IVA tests. The number of respondents who met the requirements for the IVA test was 86 respondents. This IVA test was carried out for 3 days in three different locations, then the results of 46 people were obtained with positive IVA results. Conclusion: It is hoped that the IVA test carried out on the target group that has been held will be able to raise the target group's awareness of the importance of reproductive health.